Generation of Programmatic Contents by Competencies: A Technological and Systemic View of Higher Education - Freddy Marín-González; Alexa Senior-Naveda; Luis Yamil Ferrer; Beatriz Perozo Sierralta (Frontiers in Education, 2022)
This research combines the art of designing programmatic contents by competencies and the technological variable as an innovative resource in the context of higher education. The objective of this study was focused on the development of a technological system for the generation of programmatic contents by competencies in the curricular units of university careers. This research was carried out under the empirical approach; it is of an applicative type, since it generates a proposal and it was structured methodologically by phases: Phase I of approaching the manual system and user requirements was deployed under a field design in which the current situation and user expectations were described through the techniques of participant observation and meetings of experts in the area of educational technology (teaching staff of the different academic programs, heads of departments and coordinators of the Curriculum Commission), in order to carry out business rounds as a strategy of characterization and permanent consultation of the evolution of the system design to generate agreements. Phase II led to the establishment of the structural components of the prototype, and integrated the essentials from the systems theory, software engineering, and pedagogical didactic theories. Phase III was based on the methodology of system design by prototyping. As for the results, it was evidenced that the stakeholders considered feasible the use of the system to generate programmatic contents by competence, and finally the functionality of the system and the operational advantages for the generation of programmatic contents were demonstrated.